PENERAPAN MODEL CPS BERBASIS LKS SOAL TIMSS UNTUK MENGUKUR KEMAMPUAN PEMECAHAN MASALAH - Rahmat Kamaruddin; Firdha Razak; Ahmad Budi Sutrisno (STKIP Andi Matappa, 2020)
This study aims to apply the Creative Problem Solving (CPS) learning model using TIMSS question worksheets on algebraic content to measure solving abilities. The population in this study were all VII students of SMP Negeri 1 Pangkajene totaling 180 students and a sample of 32 students who were taken using simple random technique. The instruments in this study were 1) worksheets on TIMSS questions; 2) Test problem solving skills; 3) Interview guidelines. The data will be analyzed descriptive quantitative and inferential analysis. The results obtained: 1) students 'problem solving abilities (pretest) according to the aspects assessed in the TIMSS were analyzed descriptively in moderate interpretation, which was 10 students or 33% of 32 students, while the students' problem solving abilities (posttest) were at high interpretation which was equal to 17 students or 54% of 32 students. The normalized gain test result is 0.52, which means that the increase in student learning outcomes taught by the CPS learning model is in the medium category. 2) The average percentage of students who responded positively to the application of the CPS model was 81%. 3) Inferential, the application of the CPS learning model is complete classically and has a boost to increase the gain of 0.3 or there is an increase in the average normalized gain value significantly so that this model is good for use in mathematics learning at SMP Negeri 1 Pangkajene.